A Modest Numerical Simulation for Automatic Ship Collision Avoidance System to Support Green and Autonomous Shipping Concept - Hermawan, Yuda Apri; Pratama, Fernanda Wahyu; Yulianto, Totok; Purwanto, Dedi Budi (International Journal of Offshore and Coastal Engineering (IJOCE), 2023)
The development of autonomous ship is being pursued massively and significantly, either industrially, regulatory, or academic. The autonomous ship is considered to be able to significantly reduce challenges caused by unexpected errors of manual navigation (manned ship). One of the challenges for autonomous ship development is constructing an automatic ship collision avoidance system as a basic system for identifying and avoiding an obstacle object around the ship. The collision avoidance system must consider not only the position of the ship and the obstacle but also the maneuvering characteristic (ship dynamics) and control system of the ship, thereby making its numerical system more complex. This research presents a modest numerical simulation for designing an automatic ship collision avoidance system. However, the numerical model still considers the main necessary elements of the system. The numerical model includes a set of automatic guidance system, collision avoidance system, ship dynamics, and control system. Head on head, overtaking, and crossing collision scenarios are performed to investigate the numerical model. The simulation results show that the modest numerical simulation can be used to perform an automatic ship collision avoidance system in which the ship can automatically avoid a target ship considered as the ship’s obstacle in those three collision scenarios.